Czy Muminki mogą zmienić współczesny świat? Na marginesie recenzji książki Hanny Dymel-Trzebiatowskiej Przechadzki po Dolinie Muminków. Perspektywa filozoficzno-literacka (2024) - Dorota Michułka (Zagadnienia Rodzajów Literackich)
This essay is an attempt at contextual interpretation of Hanna Dymel-Trzebiatowska’s book Przechadzki po Dolinie Muminków. Perspektywa filozoficzno-literacka (2024). The author has compiled Tove Jansson’s famous series about the Moomins in a thorough, careful and conscientious research manner, penetrating and consistent at the analytical and interpretative level, rich in reference to the international and interdisciplinary literature on the subject. Dymel- Trzebiatowska’s book treats the stories of the Moomins as a kind of philosophy of life, refers to broad existential-ethical, sociological, psychological and pedagogical contexts indicating the extraordinary timeliness and universality of the messages, axiological challenges and deeper meanings of Jansson’s stories, issues and themes relevant (including, for example, equality issues, feminist criticism, confronting the threats of modern civilization, environmental humanism, ageism, issues of communication and silence, notions of loneliness, rejection and the “struggle” for acceptance, but also irony and the role of theater), which makes it an important part of the discussion on contemporary humanistic education of children and adolescents in its broadest sense.